Population growth, employment and poverty in third world mega-cities Analytical and policy issues - Oberai, A. S. (New York, 1993)
The study deals with problems and policy options facing Third World mega-cities. It examines the major sources of urban population growth and spatial concentration and analyses the conflict between economic efficiency and decentralization. It also assesses the implications of rapid urban population growth for employment generation and poverty alleviation, discusses the relationship between urban poverty and access to housing and basic social services, and examines the problems of resource mobilization to finance urban programmes. The analysis is based on data gathered from several Third-World mega-cities. The study thus provides a comparative analysis of mega-city problems and suggests the direction in which future policies need to be developed to deal more effectively with these problems.
Keywords: Developing countries-population